From Challenge to Resource: Understanding Cross-Linguistic Influence in SLA - Lababa (Lingua : Journal of Linguistics and Language, 2024)
Cross-linguistic influence (CLI) plays a pivotal role in second language acquisition (SLA), reflecting the ways in which first language knowledge shapes subsequent language learning. This narrative review synthesizes findings from studies spanning structural, socio-cultural, technological, and individual dimensions, with the aim of offering a comprehensive understanding of CLI in multilingual contexts. Literature was retrieved from major databases, including Scopus, Web of Science, and Google Scholar, using targeted keywords such as “cross-linguistic influence,” “second language acquisition,” “bilingualism,” and “transfer effects.” Selection criteria included peer-reviewed studies published between 2000 and 2025, encompassing experimental, longitudinal, and qualitative designs. Results indicate that structural factors, such as educational policies and curricula, significantly condition transfer outcomes, with inclusive bilingual policies fostering positive transfer. Socio-cultural environments further mediate CLI by shaping learners’ linguistic exposure and practices, while technological innovations, including computational modeling and AI-driven applications, provide new insights into transfer processes though remain unevenly distributed globally. Individual cognitive traits, including metalinguistic awareness and motivation, strongly determine how learners experience CLI, influencing whether transfer becomes a barrier or a resource. These findings underscore the need for integrated strategies that combine pedagogy, policy, and technology to mitigate negative transfer and leverage positive effects. The review highlights research gaps in longitudinal analysis, multilingual repertoires, and individual differences, suggesting directions for future inquiry. Recognizing CLI as a dynamic, multidimensional process is crucial for advancing equitable and effective SLA in a multilingual world.